Scattering and dynamics of polymers : seeking order in disordered systems - Han, Charles C.; Akcasu, Ziyaeddin A.; Wiley InterScience (Online service) (Singapore : John Wiley & Sons, 2011)
"Scattering is a very powerful tool to study the structure of polymers. Written by highly regarded and respected scientists in the field, this book presents the latest developments in the field of scattering in a uniform, systematic manner. This volume arms readers with both theoretical and experimental aspects of the intended area, offering much simplified theoretical explanations on the physics of scattering. The authors provide discussion on applications of experimental techniques."--Publisher's presentation.
Front Matter -- Plane Waves, Scattering, and Polymers -- Fluctuations, Correlation, and Static/Dynamic Scattering -- Dynamics and Kinetics of Phase Separation in Polymer Systems -- Statistical Mechanical Approach to the Theory of Dynamic Scattering -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Light -- Scattering; Polymers -- Spectra; Polymers -- Rheology; Light -- Scattering; Polymers -- Rheology; Polymers -- Spectra; Electronic resource